Macroeconomic determinants of foreign direct investment (FDI) in Malaysia / Muhammad Azlan Mohd Ashhari - Mohd Asshari, Muhammad Azlan (Faculty of Business and Management, 2014)
This paper aim is to investigate the factors that influence the foreign direct investment in Malaysia. The determinants are being measure in order to know whether it affect the amount of the investment. Recently, the FDI in Malaysia shows that our country was underperforming. This situation worried our leaders because the declining of FDI could affect economic growth of Malaysia conversely. The dependent variable is foreign direct investment (FDI) and the independent variables to be used are macroeconomic factors which are gross domestic product (GDP), interest rate (IR), exchange rate (ER), inflation rate (IR), unemployment rate (UR), company tax (CT) and labour cost (LC) . The study is an attempt to investigate and examine the performance of foreign direct investment in Malaysia over 2000 – 2013 by using the quarterly basis of time series of the variables will be collected from the Thomsonone data stream website. Multiple regression analysis will be used in order to reveal about the relationships between the dependent and the independent variables that has been chosen or pick by me. The result of this paper would provide us with the indicate view and the macroeconomic factors that can affect the foreign direct investment in Malaysia.